Application of PCR – RFLP markers for identification of genetically delimited groups of the Calypogeia fissa complex (Jungermanniopsida, Calypogeiaceae) - Buczkowska, Katarzyna (Biodiversity: Research and Conservation, 2015)
Currently, two subspecies are formally recognized within Calypogeia fissa: C. fissa subsp. fissa occurring in Europe and C. fissa subsp. neogea known from North America. Genetic studies have revealed a complex structure of this species. Within the European part of distribution, three genetically distinct groups PS, PB and G are distinguished. The combination of the SCAR marker Cal04 and PCR-RFLP markers with three restriction enzymes (SmaI, TaqI and TspGWI) allowed the recognition of all groups within the C. fissa complex. The TaqI enzyme recognizing the restriction sites in the PCR product of SCAR marker Ca104 turned out to be the best marker